Safeguarding public health concerns, livelihoods and productivity in wastewater irrigated urban and periurban vegetable farming - Abaidoo, Robert C.; Keraita, Bernard N.; Amoah, Philip; Drechsel, Pay; Bakang, J.A.; Kranjac-Berisavljevic, Gordana; Konradsen, Flemming; Agyekum, W.; Klutse, A. (CGIAR Challenge Program on Water and Food, 2009)
The goal of the project was to develop integrated and user-oriented strategies to safeguard public health concerns without compromising livelihoods and land and water productivity in wastewater irrigated urban and peri-urban vegetable farming. In this project, assessment of land and water productivity in wastewater irrigated farming was done, levels of contamination on irrigation water and vegetables quantified at different levels along the food chain (farms, markets and consumer level) and appropriate lowcost risk reduction strategies identified and participatory testing done with stakeholders at farm and consumer levels. A large number of students were involved in the project, significantly building human capacity